HARIDSYAH BATUBARA, SH. NIM. A.21213021 - HARIDSYAH BATUBARA, SH. NIM. A.21213021, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThe thesis is the implementation of good governance in the implementation of procurement of goods and services (public works studies in the province of West Kalimantan). The method used in this research is normative sociological approach. From the results of this thesis research we concluded that adoption of good governance in the procurement of government goods and services at the Department of Public Works of West Kalimantan Province is generally guided by the Regulation of the President of the Republic of Indonesia Number 4 Year 2015 On the Fourth Amendment to the Presidential Regulation No. 54 Year 2010 On Procurement goods / Services. From the results of this thesis research we concluded that adoption of good governance in the procurement of government goods and services at the Department of Public Works of West Kalimantan Province is generally guided by the Regulation of the President of the Republic of Indonesia Number 4 Year 2015 On the Fourth Amendment to the Presidential Regulation No. 54 Year 2010 On Procurement goods / Services. To carry out the function of supervision over government procurement, West Kalimantan Governor issued a circular on the general user activity management APBD / APBN / L in the Provincial Government Kalimantan Barat.Kendala-constraints faced by the Public Works Department in the province of West Kalimantan implementation of public auction tender the procurement of goods and services among others, lack of personnel from agencies who have passed the certification of procurement of goods and services; conflict of auction schedule with personnel coming from outside agencies; lack of effective technical team to correct or check the planning document; HR services provider less. That the efforts of Public Works Department of West Kalimantan Province took a strategic policy to address various problems in implementing Tata Keperintahan good in the procurement of government goods and services at the Department of Public Works of West Kalimantan Province, following that the Department of Public Works and Government of West Kalimantan Province formed a steering committee for Development West Kalimantan Province which carry team Principal Duties and Functions include guidance and control Development of West Kalimantan Province, especially the procurement of goods and services. West Kalimantan Provincial Government has implemented a performance-based budgeting. Application of performance indicators is expected to boost the accountability of government procurement. To avoid inflation (Mark-Up) costs in the stage of budgeting and preparation of Self-Estimated Price (HPS) procurement of goods and services, the Government of West Kalimantan Province issued the West Kalimantan Governor2Number 58 Year 2015 on the Standard Cost and Unit Price Regional Shopping West Kalimantan .Dinas public Works and Government of West Kalimantan monitoring and evaluation of all activities of procurement, West Kalimantan Provincial Government through the Bureau of Development Secretariat of West Kalimantan Province allocates funds for education and training certification morning procurement employees on the environment Agency Public Works West Kalimantan Province. West Kalimantan provincial government establishes Daily Newspapers Newspaper Thanks as West Kalimantan Province to the announcement of procurement of goods and services of the provincial government of West Kalimantan.Keywords: Implementation, Procurement, goods and services.ABSTRAKTesis ini penerapan tata kelola pemerintahan yang baik dalam penyelenggaraan pengadaan barang dan jasa ( studi di dinas pekerjaan umum provinsi Kalimantan Barat). Metode pendekatan yang digunakan dalam penelitian ini adalah pendekatan normatif sosiologis. Dari hasil penelitian tesis ini diperoleh kesimpulan Bahwa Penerapan tata kepemerintahan yang baik dalam pengadaan barang dan jasa pemerintah pada Dinas Pekerjaan Umum Provinsi Kalimantan Barat secara umum berpedoman pada Peraturan Presiden Republik Indonesia Nomor 4 Tahun 2015 Tentang Perubahan Keempat Atas Peraturan Presiden Nomor 54 Tahun 2010 Tentang Pengadaan Barang/Jasa. Untuk melaksanakan fungsi pembinaan dan pengawasan pengadaan barang dan jasa pemerintah, Gubernur Kalimantan Barat mengeluarkan surat edaran tentang petunjuk umum pengelolaan kegiatan sumber dana APBD/APBN/L di lingkungan Pemerintah Provinsi Kalimantan Barat.Kendala-kendala yang dihadapi oleh Dinas Pekerjaan Umum Provinsi Kalimantan Barat dalam pelaksanaan lelang umum tender pengadan barang dan jasa antara lain kurangnya jumlah personel dari instansi yang dinyatakan lulus sertifikasi pengadaan barang dan jasa; adanya benturan jadwal lelang dengan personel yang berasal dari instansi dari luar; kurang efektifnya tim teknis yang mengkoreksi atau memeriksa dokumen perencanaan; SDM dari penyedia jasa kurang. Bahwa upaya Dinas Pekerjaan Umum Provinsi Kalimantan Barat mengambil kebijakan strategis untuk mengatasi berbagai permasalahan dalam penerapan Tata Keperintahan yang baik dalam pengadaan barang dan jasa pemerintah pada Dinas Pekerjaan Umum Provinsi Kalimantan Barat, sebagai berikut bahwa Dinas Pekerjaan Umum dan Pemerintah Provinsi Kalimantan Barat membentuk Tim Pembina Pembangunan Provinsi Kalimantan Barat yang melaksanakan Tugas dan Fungsi Pokok Tim ini antara lain melakukan pembinaan dan pengendalian Pembangunan Provinsi Kalimantan Barat khususnya pelaksanaan pengadaan barang dan jasa. Pemerintah Provinsi Kalimantan Barat telah menerapkan anggaran berbasis kinerja. Penerapan indicator kinerja diharapkan dapat mendongkrak akuntabilitas pengadaan barang dan jasa pemerintah.Untuk menghindari penggelembungan (Mark-Up) biaya dalam tahap penganggaran dan penyusunan Harga Perkiraan Sendiri (HPS) pengadaan barang dan jasa, maka Pemerintah Provinsi Kalimantan Barat menerbitkan Peraturan Gubernur Kalimantan Barat Nomor 58 Tahun 2015 tentang Standar Biaya dan Harga Satuan Belanja Daerah Provinsi Kalimantan Barat.Dinas Pekerjaan umum dan Pemerintah Provinsi Kalimantan Barat melakukan monitoring dan evaluasi terhadap semua kegiatan pengadaan barang dan jasa,Pemerintah Provinsi Kalimantan Barat melalui Biro3Pembangunan Sekretariat Provinsi Kalimantan Barat menganggarkan dana untuk kegiatan pendidikan dan latihan sertifikasi pengadaan barang dan jasa pagi pegawai yang ada dilingkungan Dinas Pekerjaan Umum Provinsi Kalimantan Barat. Pemerintah Provinsi Kalimantan Barat menetapkan Surat Kabar Harian Berkat sebagai Surat Kabar Provinsi Kalimantan Barat untuk pengumuman proses pengadaan barang dan jasa pemerintah provinsi Kalimantan Barat.Kata Kunci:Penyelenggaraan, Pengadaan, Barang Dan Jasa.